Investigating audience preferences within the hybrid competitive-comedic format of taskmaster UK - David Haim Silver (PLoS ONE, 2025)
Background: Hybrid entertainment formats combining competitive and comedic elements present opportunities to investigate factors driving audience engagement. I analyzed Taskmaster UK (2015–2023), a BAFTA-winning comedy panel show where comedians compete in creative tasks judged by a host, to quantify relationships between scoring mechanics, performer characteristics, and viewer ratings. Methods: I analyzed 154 episodes encompassing 917 tasks performed by 90 contestants, with audience reception measured through 32,607 IMDb votes. To capture scoring dynamics while avoiding intercorrelated metrics, I employed a low-dimensional representation using mean (μ) and variance (σ2) of score distributions. Additional methods included mixture modeling for rating distributions (tri-peak model: a1·δ(1)+a10·δ(10)+agaussian·𝒩(μ,σ)), hierarchical clustering for performance patterns, and Random Forest regression. All p-values include False Discovery Rate correction. Results: Low-dimensional scoring representation showed no significant associations with IMDb ratings (μ: r = −0.012, p = 0.890; σ2: r = −0.118, p = 0.179; combined R2 = 0.017, p = 0.698). Contestant age emerged as the strongest predictor (39.5% ± 2.1% feature importance). Sentiment analysis identified increased awkwardness over time (β=0.0122, adjusted p = 0.0027). Clustering revealed five performance archetypes appearing consistently across series. Geometric analysis showed 38.9% (98/252) of mathematically possible scoring distributions occur in practice. Conclusions: Competitive elements provide framework while audience engagement correlates with performer characteristics and emotional content. The low-dimensional scoring analysis eliminates methodological concerns about metric intercorrelation. These findings position Taskmaster UK as a quantifiable example where secondary mechanics enable but do not determine primary value.